Low-resistive, CMOS-compatible ohmic contact schemes to moderately doped n-InP. (17th May 2017) - Hahn, Herwig; Sousa, Marilyne; Czornomaz, Lukas
Abstract: III-V laser integration on Si is seen as a promising path to overcoming the current interconnect bottleneck in computing. Therefore, III-V lasers need to be integrated with a CMOS-compatible process flow. Furthermore, parasitic elements of the lasers must be minimized while preventing trade-offs to the lasing action (i.e. doping level in the 10 18 cm −3 ). One such parasitic element is the n-type ohmic contact on moderately doped n-InP. A detailed study of CMOS-compatible contacts on n-InP including structural analysis has not yet been performed. To fill this gap, we will comprehensively report on various metal contacts on n-InP that reach a record-low median specific contact resistivity of 6  ×  10 −8 Ω · cm 2 and on contacts that show very shallow alloying behavior while still offering a specific contact resistivity in the very low 10 −7 Ω   ⋅ cm 2 range.